2006
DOI: 10.4142/jvs.2006.7.4.315
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical localization of calcium binding proteins and some neurotransmitters in myenteric plexus of goat stomach

Abstract: To understand the neurochemical properties of the gastric myenteric plexus of ruminants, the expression patterns of calbindin D-28k (CB), calretinin (CR), substance P (SP) and calcitonin gene-related peptide (CGRP) were explored in the Korean native goat. In gastric myenteric plexus, CB and SP immunoreactivity were observed in round- or oval-shaped neurons. CR and CGRP immunoreactivity were detected only in the nerve fibers. This immunohistochemical localization of CB, CR, CGRP and SP in the myenteric plexus o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Some studies point to afferent innervation of the ruminal epithelium by CALB‐expressing neurons. In this regard, Lee & Nam (2006) suggested that CALB immunoreactive neurons were intrinsic primary afferent neurons in the goat forestomach. In cattle, SP immunoreactive neurons were thought to have intrinsic afferent functions (Kitamura et al.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies point to afferent innervation of the ruminal epithelium by CALB‐expressing neurons. In this regard, Lee & Nam (2006) suggested that CALB immunoreactive neurons were intrinsic primary afferent neurons in the goat forestomach. In cattle, SP immunoreactive neurons were thought to have intrinsic afferent functions (Kitamura et al.…”
Section: Discussionmentioning
confidence: 99%